Renal Function and Urinary Biomarkers in Cardiac Bypass Surgery: A Prospective Randomized Trial Comparing Three Surgical Techniques - Deininger, Stefanie; Hoenicka, Markus; Müller-Eising, Kristina; Rupp, Patricia; Liebold, Andreas; Koenig, Wolfgang; Gorki, Hagen (The Thoracic and Cardiovascular Surgeon, 2016)
Background Cardiopulmonary bypass procedure is associated with an increased risk of renal impairment. To which extent structural damage causes functional decline is unknown. We evaluated perioperative kidney injury and function in patients treated with conventional extracorporeal circulation (CECC), minimized extracorporeal circulation (MECC), and off-pump coronary artery bypass grafting (OPCAB).Methods Blood and urine samples, collected at baseline and up to 72 hours after surgery from patients of the HEPCON trial (DRKS00007580, 120 patients randomized for heparin management and for surgical technique), were analyzed for differences in renal injury and function. Neutrophil gelatinase-associated lipocalin, α glutathione S-transferase, liver fatty acid-binding protein, and kidney injury molecule-1 were measured as urinary protein markers of renal tubular injury. Serum creatinine, blood urea levels, and estimated glomerular filtration rate were determined to monitor renal function.Results Markers of tubular injury differed significantly between surgical technique groups early after surgery, indicating the most detrimental effect in CECC. Hemolysis and hemodilution correlated with these early changes. A late rise did not show intergroup differences. Time courses of renal function parameters, as well as the development of acute kidney injury in 15 patients (13.5%), were irrespective of surgical technique. Heparin management did not influence renal parameters.Conclusion During coronary artery bypass grafting, CECC temporarily induces more tubular injury than MECC or OPCAB. However, late changes of renal function parameters occur irrespective of extracorporeal perfusion mode and even in off-pump surgery.
Keywords: coronary artery bypass grafting; cardiopulmonary bypass; kidney; off-pump surgery